Effect of Cu-Fe-Co Catalyst Pretreatment in Higher Alcohol Synthesis - Aho, Atte; Simakova, Irina; Sandri, Francesco; Peuronen, Anssi; Lindberg, Daniel; Mäki-Arvela, Päivi; Eränen, Kari; Lastusaari, Mika; Murzin, Dmitry Yu (Springer Nature, 2026)
Higher alcohol synthesis was carried out over a CuFeCoK/SiO2 catalyst with the focus on catalyst pretreatment methods. These methods consisted of either reduction with hydrogen, or reduction followed by low temperature carburization with CO, all at 300 °C. Furthermore, a third method was applied without any pretreatment of the catalyst. It was found that the pretreatment using both reduction and carburization gave the most active catalyst in terms of CO conversion within the temperature range tested, 225–300 °C. The apparent activation energy for CO conversion was calculated to be ca. 79 kJ/mol for different pretreatment methods. The pretreatments influenced the product distribution in a way that more alkenes were formed with the reduced and carburized catalyst compared to the catalysts pretreated with the other procedures, while the selectivity to CO2 was the highest for the only reduced catalyst. The highest selectivity (58.5%) to alcohols was achieved with the un-pretreated catalyst although at the lowest CO conversion, being as low as 4.3% at 225 °C. No catalyst deactivation was observed during testing of the catalysts up to 100 h time on stream independent of the pretreatment method. The theoretical equilibrium compositions was calculated for the different pretreatment methods and compared with catalyst characterisation results.